Additive QTLs on three chromosomes control flowering time in woodland strawberry (Fragaria vesca L.). (24th May 2017) - Samad, Samia; Kurokura, Takeshi; Koskela, Elli; Toivainen, Tuomas; Patel, Vipul; Mouhu, Katriina; Sargent, Daniel James; Hytönen, Timo
Abstract: Flowering time is an important trait that affects survival, reproduction and yield in both wild and cultivated plants. Therefore, many studies have focused on the identification of flowering time quantitative trait locus (QTLs) in different crops, and molecular control of this trait has been extensively investigated in model species. Here we report the mapping of QTLs for flowering time and vegetative traits in a large woodland strawberry mapping population that was phenotyped both under field conditions and in a greenhouse after flower induction in the field. The greenhouse experiment revealed additive QTLs in three linkage groups (LG), two on both LG4 and LG7, and one on LG6 that explain about half of the flowering time variance in the population. Three of the QTLs were newly identified in this study, and one co-localized with the previously characterized FvTFL1 gene. An additional strong QTL corresponding to previously mapped PFRU was detected in both field and greenhouse experiments indicating that gene(s) in this locus can control the timing of flowering in different environments in addition to the duration of flowering and axillary bud differentiation to runners and branch crowns. Several putative flowering time genes were identified in these QTL regions that await functional validation. Our results indicate that a few major QTLs may control flowering time and axillary bud differentiation in strawberries. We suggest that the identification of causal genes in the diploid strawberry may enable fine tuning of flowering time and vegetative growth in the closely related octoploid cultivated strawberry. Abstract : Soft fruit: Extending the strawberry season A genetic study of wild strawberry highlights genes that could be used to make cultivated varieties flower and fruit earlier in the year. A longer fruiting season is the 'holy grail' of strawberry growers, and has been approached from two directions. Most studies have focused on producing 'everbearing' varieties, which flower and fruit all year. Timo Hytönen at University of Helsinki, Finland, and an international team of colleagues took a second approach: bringing forward the start of the flowering season. They used statistical analysis to identify genes that affect flowering time in wild, woodland strawberry, and found four that act additively to influence time of first flowering. The team proposes that variation in the same genes in cultivated strawberries could be manipulated to prolong their flowering season.